Resistência genotípica primária do H.pylori à claritromicina e associação com genótipos de virulência do H.pylori no nordeste do Brasil - Benígno, Tiago Gomes da Silva (2020)
H.pylori resistance to clarithromycin is considered to be one of the main factors responsible for failure to eradicate H.pylori. The prevalence of resistance to clarithromycin may vary according to the region analyzed. This work seeks to assess the prevalence of primary genotypic resistance of H. pylori to clarithromycin using the RT-PCR molecular method and to verify its association with virulence genotypes of H.pylori strains in Northeastern Brazil. This study was carried out at the Walter Cantídeo University Hospital of the Federal University of Ceará and in the urban community, Parque Universitário. 260 dyspeptic patients who underwent endoscopy and were positive for H.pylori through histology, urease and PCR (gastric biopsy) were evaluated. This study also involved 40 asymptomatic community residents aged ≤ 18 years and positive for H.pylori by breathing test and CRP (gastric juice obtained by enterotest). All untreated individuals. Including those in which the 23s rRNA gene was present in the PCR. Resistance to clarithromycin was identified through mutation points A2143G and A2142G in the 23s rRNA gene by RT-PCR. The genes cagA, cagE, vacA (alleles) and ice A (alleles) of H.pylori were identified by PCR using specific primers. Of the 300 individuals positive for H.pylori, 222 (74%) were positive for 23s rRNA. 198 adults (56.06% female and 43.94% male, age 47.95 ± 14.53 years) and 24 asymptomatic in the community (50% male and 50% female, age 12.92 ± 03 years). We found that the primary resistance to clarithromycin was 14.4% (32/222). 14.2% in adults and 12% in children. There was no association of point mutations with sex, age or gastric disease. The most common point mutation was A2143G / A2147G (62.50%), followed by A2142G / A2146G (37.5%) and 12.5% double mutation. They were heteroresistant (strains with mutant and wild allele) 43.75% (14/32). The prevalence of cagA strains was 75.5% (167/222). Point mutations were present in 11% (19/167) of positive cagA strains and 23% (13/55) of cagA negative strains. Resistance was significantly associated with negative cagA status (p 0.025 OR: 0.4; I.C 95% 0.189-0.909). The prevalence of the cagE gene was 61% (136/222). Point mutations were present in 10% (14/136) of the cagE positive strains and 21% (18/85) of the cagE negative strains. Resistance was significantly associated with negative cagE status (p 0.025 OR: 0.4; I.C 95% 0.200-0.913). There was no association between iceA1, iceA2, vacA and alleles with point mutations in the 23s rRNA gene. We concluded that the primary genotypic resistance of H. pylori to clarithromycin was 14.41% and that it is within the range for the empirical use of triple therapy containing clarithromycin. The most prevalent mutation point was A2143G. The positive cagA and cagE strains had a lower prevalence of resistance to clarithromycin. Hence, H.pylori resistance to clarithromycin was most often found in individuals colonized with less virulent strains.